Validity and Reliability of the Korean Version of the Weight Self-Stigma Questionnaire (WSSQ-K) - Seyoen Park; Kawoun Seo (MDPI AG, 2023)
Weight self-stigma refers to negative self-prejudice due to the internalization of negative social messages about one's weight. People with high self-stigma may have low self-esteem and decreased social activity. Weight-related self-stigma can create diet-related disorders since it is highly related to the recognition of body types. However, there are no tools available to measure the weight-related stigma of the general public in Korea. This study evaluated the validity and reliability of the Korean version of the Weight Self-Stigma Questionnaire (WSSQ-K). A methodological study was conducted with 150 Korean university students. Construct validity was evaluated using exploratory factor analysis. The WSSQ-K was correlated with body mass index and measures of self-esteem and weight concern to evaluate concurrent validity. Internal consistency reliability was evaluated with Cronbach's alpha. In the exploratory factor analysis, two factors were proposed: "self-devaluation" (Cronbach's α = 79) and "fear of enacted stigma" (Cronbach's α = 82). Factor loadings for the 12 items on two factors ranged from 0.539 to 0.811, which explained 53.3% of the total variance. The WSSQ-K correlated with body mass index, self-esteem, and weight concern. The findings showed that the WSSQ-K was a reliable and valid measure that could be used for evaluating weight self-stigma in normal-weight adults in Korea.